Challenges in Implementing Differentiated Learning Under the Kurikulum Merdeka: A Qualitative Study of Elementary School Teachers - Glorya Pashya Koela; Yun Ratna Lagandesa; Sisriawan Lapasere; Rizal; Rangga Putera Boroallo (Papanda Publisher, 2026)
Despite the increasing adoption of differentiated learning under Indonesia's Kurikulum Merdeka, the practical challenges faced by elementary school teachers in implementing this approach—particularly within resource-constrained public school settings—remain insufficiently documented. This study employed a descriptive qualitative design to investigate the challenges, adaptive strategies, and student outcomes associated with differentiated learning implementation at SD Inpres 3 Talise, Palu City, Central Sulawesi. Data were collected through semi-structured interviews, structured classroom observations, and document analysis involving six purposively selected classroom teachers during the 2025/2026 academic year. Data analysis followed the interactive model of Miles et al. (2014), with trustworthiness established through methodological triangulation and member checking. Three principal challenges were identified: limited instructional time (cited by all six participants), large class sizes, and low levels of student self-directed learning. Teachers employed three primary adaptive strategies: digital platform use, collegial collaboration, and reliance on institutional support. A notable finding was the near-absence of formally differentiated assessment rubrics, revealing a significant assessment-instruction alignment gap. These findings extend the international literature by identifying student self-directedness as an internally generated pedagogical constraint that is underexplored in differentiation frameworks. The study underscores the need for professional development programs targeting assessment differentiation and calls for structural reforms to support sustainable differentiated instruction in Indonesian elementary education.